Rumination and Identity Confusion as Predictors of Emotional Exhaustion in Emerging Adult Women - Al-Taie, Zainab; El-Sayed, Mona (Psychology of Woman Journal, 2025)
Objective: This study aimed to investigate the predictive roles of rumination and identity confusion in emotional exhaustion among emerging adult women.Methods and Materials: A correlational descriptive research design was employed, involving a sample of 410 emerging adult women from Egypt. The participants were selected based on Morgan and Krejcie’s sample size table to ensure adequate statistical power. Standardized self-report instruments were used to measure emotional exhaustion, rumination, and identity confusion. Data were analyzed using SPSS version 27. Descriptive statistics were calculated, and Pearson correlation coefficients were computed to examine the relationships between the dependent variable and each independent variable. A standard linear regression analysis was then conducted to assess the joint predictive value of rumination and identity confusion on emotional exhaustion, and to determine the unique contribution of each predictor.Findings: The results indicated that both rumination (r = .58, p < .01) and identity confusion (r = .51, p < .01) were significantly and positively correlated with emotional exhaustion. Multiple regression analysis revealed a significant predictive model, F(2, 407) = 148.62, p < .001, with an R² of .41. Rumination (β = .46, p < .001) and identity confusion (β = .31, p < .001) both contributed significantly to the model, indicating that each variable uniquely predicted emotional exhaustion among the participants.Conclusion: These findings suggest that rumination and identity confusion are critical psychological factors contributing to emotional exhaustion in emerging adult women. Interventions that target maladaptive cognitive styles and promote identity clarity may be essential in reducing emotional fatigue during this life stage.